Pengaruh Sarana dan Prasarana dalam Pembelajaran di RA Nurhidayah - Tiara Angelly; Syazkia Salsabilla Rais; Nadia Meilita; Putri Rizky Amanda (Universitas Muhammadiyah Enrekang, 2022)
Educational facilities and infrastructure include all equipment and facilities used during the teaching process, both movable and immovable, such as desks, classrooms and computers. The functions of educational infrastructure include (a) accelerating knowledge from teacher to students, (b) making it easier for students to capture the big picture of what they are learning, and (c) fostering a sense of togetherness among groups of students. This study uses a qualitative descriptive approach to collect data on the use and maintenance of educational resources in schools. RA Nurhidayah almost meets learning standards.